ОБ ЭКОЛОГИИ ЯЗЫКА НАШИХ УЛИЦ - Кощанов, К.М.; Гайратова, Ш.; Назарова, З.С. (SCIENCE and SOCIETY, 2020)
The article deals with the purity and development of the spoken language and modern advertisements.